2017
DOI: 10.1371/journal.pone.0183471
|View full text |Cite
|
Sign up to set email alerts
|

Mixed methods research in tobacco control with youth and young adults: A methodological review of current strategies

Abstract: IntroductionTobacco use among young people is a complex and serious global dilemma that demands innovative and diverse research approaches. The purpose of this methodological review was to examine the current use of mixed methods research in tobacco control with youth and young adult populations and to develop practical recommendations for tobacco control researchers interested in this methodology.MethodsUsing PubMed, we searched five peer-reviewed journals that publish tobacco control empirical literature for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…In line with findings reported in recent reviews [8,26,34], many articles reported a convergent design and cited complementarity as the main rationale for mixing methods. In these studies, the findings of the quantitative and the qualitative components were used to enrich or elaborate on the findings of the other component or to provide further insights.…”
Section: Main Findingssupporting
confidence: 79%
See 2 more Smart Citations
“…In line with findings reported in recent reviews [8,26,34], many articles reported a convergent design and cited complementarity as the main rationale for mixing methods. In these studies, the findings of the quantitative and the qualitative components were used to enrich or elaborate on the findings of the other component or to provide further insights.…”
Section: Main Findingssupporting
confidence: 79%
“…We examined the relationship between type of design and study purpose since these two elements are closely associated, as frequently stated in the mixed methods literature [20,26]. Table 5 shows a significant relationship (p < 0.001) between the study purpose and the type of mixed methods used: while convergent and explanatory sequential designs were used mainly for evaluating interventions or investigating research topics in palliative care, exploratory sequential, and multistage designs were generally employed to develop a tool, a quantitative instrument, or an intervention.…”
Section: Mixed Methods Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco use is not restricted to individual's behaviour but is a multifaceted process contributed by a varied range of factors such as social, environmental, psychological and the genetic factors which are linked to the tobacco use 15 . The determinants associated with SLT consumption include gender, wealth index (inverse association) and association with scheduled tribe 16 .…”
Section: Determinants For Slt Usementioning
confidence: 99%
“…This was a methodological study [21] and was conducted to design a questionnaire for assessing mothers' sex education ability to preschool children in Iran, in 2018. In this study, only interviews with mothers were used due to the fact that in Iran mothers are culturally responsible for the education of children, although the new educational evidence in the world emphasizes the responsibility of parents in educating children.…”
Section: Design and Data Collectionmentioning
confidence: 99%